2017
DOI: 10.1038/s41598-017-08413-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences of protein expression profiles, KRAS and BRAF mutation, and prognosis in right-sided colon, left-sided colon and rectal cancer

Abstract: To compare protein expression levels, gene mutation and survival among Right-Sided Colon Cancer (RSCC), Left-Sided Colon Cancer (LSCC) and rectal cancer patients, 57 cases of RSCC, 87 LSCC and 145 rectal cancer patients were included retrospectively. Our results demonstrated significant differences existed among RSCC, LSCC and rectal cancer regarding tumor diameter, differentiation, invasion depth and TNM stage. No significant difference was identified in expression levels of MLH1, MSH2, MSH6, PMS2, β-Tubulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 45 publications
0
35
3
1
Order By: Relevance
“…Patients with right-sided tumours have longer recurrence-free survival than those with left-sided tumours, but at recurrence the course of the disease seems to be more complicated with shorter OS 30 . The right colon, evolving from the mid gut, and the left colon, evolving from the hind gut, are physiologically distinct and may also differ in genetic and immunopathological characteristics 32,33 . The right colon, evolving from the mid gut, and the left colon, evolving from the hind gut, are physiologically distinct and may also differ in genetic and immunopathological characteristics 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with right-sided tumours have longer recurrence-free survival than those with left-sided tumours, but at recurrence the course of the disease seems to be more complicated with shorter OS 30 . The right colon, evolving from the mid gut, and the left colon, evolving from the hind gut, are physiologically distinct and may also differ in genetic and immunopathological characteristics 32,33 . The right colon, evolving from the mid gut, and the left colon, evolving from the hind gut, are physiologically distinct and may also differ in genetic and immunopathological characteristics 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…RCOAD is related to KRas and Serine/ threonine-protein kinase B-raf (BRAF) mutations of defect mismatch repair genes and microRNA-31, while LCOAD is closely associated with chromosome instability, p53, NRas, and microRNA-146a, microRNA-147b, and microRNA-1288 [10]. However, Gao et al [11] showed no significant difference in the expression levels of MLH1, MSH2, MSH6, PMS2, β-tubulin III, p53, Ki67, topoisomerase Iiα, and BRAF gene mutations between the two types of COAD. A number of studies have reported significant differences in p53 gene mutation and protein expression between RCOAD and LCOAD [12][13][14], while another study has shown no significant correlation between p53 protein expression and tumor location [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, traditionally, patients with distal colon and rectal cancer have frequently been grouped together in clinical or scientific research. However, there is increasing evidence that distal colon and rectal cancer are related to each other but are distinct in regard to their clinical behavior, including the patterns of metastasis, response to treatment and clinical outcome (5)(6)(7). However, to the best of our knowledge, the underlying biological carcinogenic backgrounds of the two types of cancer have not been investigated.…”
Section: Introductionmentioning
confidence: 99%